How Americans Talk about Separation of Church and State: Moral Frameworks of Justice and Care. Issue 2 (3rd April 2021) - Hull, Kathleen E.; Edgell, Penny
ABSTRACT: This paper draws on data from 12 focus group discussions of a faith-based prison ministry program to examine how ordinary Americans talk about the separation of church and state. The focus groups – conducted in Houston, Minneapolis-St. Paul, and Boston – revealed that program supporters and opponents draw on different moral frameworks, with supporters focusing on a framework of care and opponents focusing on a framework of justice. The findings affirm the centrality of moral concerns in shaping citizen stances on church-state separation and suggest that meaningful political compromise is possible on the issue of government support of faith-based social services.